Supply Chain Management Issues in the European Horsemeat Scandal - Li, Lingxiao (2013)
In early 2013, Europe horsemeat scandal issue has pulled public and media’s attention to the food safety and fraud problem. To find ways to prevent them happen, this dissertation has analyzed and discussed the possible food supply chain improvement plans based on Europe horsemeat scandal. The research has found that the apparent causes of this scandal are food supply chain complexity, imbalanced bargaining power and food price analysis deficiency, and immoderate trust between supply chain members but the root causes are non-transparent supply chain and improper relationship building. To improve supply chain transparency and strengthen supply chain members’ relationship, solutions are short the food chain which aim to keep supply chain simple to improve supply chain traceability and control power, build proper cooperative relationship between supply chain members which could improve supply chain transparency and avoid immoderate trust and finally apply information system and apply RFID technology that will give those methods support and improve implementation efficiency.